Regulating Analysts: NASD Rule 2711's Impact on Market Reaction and Liquidity Changes Surrounding Coverage Initiations - RANASINGHE, Tharindra (Institutional Knowledge at Singapore Management University, 2012)
We investigate the net effect of NASD Rule 2711 on information intermediary role of analysts by examining the market reaction and changes in liquidity surrounding coverage initiations in the pre- and post- regulation periods. This regulation was intended to eliminate conflict of interests faced by analysts with investment banking ties, but it has in essence blocked information flow between research and investment banking functions. We document that coverage initiations in the post-regulation period evoke stronger market reactions and greater liquidity improvements for firms with high pre-existing analyst coverage. These results indicate that the benefits of NASD Rule 2711 are mainly confined to firms with richer information environments. Further analyses reveal that these results are more pronounced for growth firms, suggesting that the benefits of the regulation are greater when the potential for conflict of interests is higher.